2013
DOI: 10.1007/s00520-013-1991-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of general symptom level, specific adverse events, treatment patterns, and patient characteristics on health-related quality of life in patients with multiple myeloma: results of a European, multicenter cohort study

Abstract: PurposeNovel multiple myeloma (MM) therapies have increased patient longevity but are often associated with notable symptom burden. This study quantified the effect of general symptom level, specific symptoms, and treatment-related adverse events (AEs) on MM patients’ health-related quality of life (HRQoL).MethodsThe European Organization for Research and Treatment of Cancer (EORTC) generic cancer questionnaire (Quality of Life Questionnaire Core 30) and MM-specific questionnaire (QLQ-MY20) were used in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
98
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 28 publications
10
98
2
2
Order By: Relevance
“…HRQoL decreases as burden of illness increases over time with progression of disease. 1,2 Patients often complain of fatigue and pain, 3,4 and frequently show symptoms of emotional distress, such as anxiety and depression. Impairment in physical and emotional functioning is well described in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…HRQoL decreases as burden of illness increases over time with progression of disease. 1,2 Patients often complain of fatigue and pain, 3,4 and frequently show symptoms of emotional distress, such as anxiety and depression. Impairment in physical and emotional functioning is well described in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of SREs has been linked to inferior survival [5,6], reduced quality of life [7], and increased healthcare costs for patients with MM [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of fatigue and pain are interrelated, as pain decreases physical activity and negatively affects performance status, mood and sleep, resulting in increased fatigue [25]. A cohort study and cross-sectional analysis of patients with MM reported that disease duration, symptom burden, bone symptoms, and being currently on therapy were strong predictors of global health status on multiple regression analyses [26]. Anemia also has a known adverse impact on physical functioning and QoL variables including fatigue [27], which can drive patients to abandon treatment [28]; it also leads to other symptoms that adversely affect patients' physical status, functional capacity, and overall QoL [29].…”
Section: Discussionmentioning
confidence: 99%